Media loose parts: Optimising fine motor skills and pre-writing readiness in early childhood - Hajrawati, Yunika; Mufassirul Alam (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: This research is motivated by the low fine motor skills of children aged 4-5 at RA Al Khairiyah Koja due to insufficient stimulation and unengaging learning media. Objective: The study aims to evaluate the effectiveness of using loose parts media to improve children's fine motor skills, specifically focusing on pre-writing readiness. Methods: The method employed is Classroom Action Research (CAR) using Kurt Lewin's model, conducted over two cycles during a four-week period with 22 students as subjects. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, description, and verification. Result: The results show a significant improvement in children's fine motor skills, where the success rate in the pre-action stage was only 9.09%, increasing to 45.45% in Cycle I, and exceeding the 75% minimum success criteria in Cycle II reaching 86.36%. Conclusion: The study concludes that loose parts media is highly effective in training finger flexibility and hand-eye coordination through explorative learning. This research contributes to the development of sustainable pedagogical tools in early childhood education by providing a cost-effective alternative to conventional materials.